(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the pattern of antibiotic use among different wards of a high-complexity university hospital. Methods: Descriptive study conducted at the Hospital das Clínicas da Faculdade de Medicina de Ribeirão Preto. Clinical and drugs utilization data of inpatients, aged 18 years or older, who received antibiotic prescriptions in 2014 were collected in the medical record and electronic prescription. Antibiotic prescriptions were classified into empirical treatment (ET) and targeted treatment (DT), and their consumption was calculated using the defined daily dose per 1,000 patient-days. The presentation of antibiotic consumption was performed using the method Drug Utilization 90%. Results: 4,102 individuals were prescribed antibiotics for therapeutic purposes. 63,985 (84.6%) of the prescriptions were classified as ET, and 11,660 (15.4%) prescriptions were classified as DT. 4th generation cephalosporins and glycopeptides are among those that accounted for 90% of utilization in all wards. In the DT group, antibiotics with a broad spectrum of action maintain high consumption in the units, such as carbapenems, the most used in three units, and polymyxin the most used in the intensive care unit. On the other hand, beta-lactamase resistant penicillins started to be represented in a greater number of wards compared to ET. Conclusion: The antibiotic utilization pattern suggests the hypothesis that antibiogram tests are being performed with the aim of investigating the bacterial sensitivity profile when there is therapeutic failure, and not to de-escalate treatment.